Children with visual disabilities in situations of playing in kindergarten - Rocha, Keuri Costa Carvalhais da (2015)
This research investigated the participation of children with visual disabilities in the contexts of playing in kindergarten. It was based on Vigotski’s historical and cultural perspective of human development as it assigns a role in social relations and considers them a subsidy in the construction of playing. The study was held at a daycare’s nursery class in a town of the Metropolitan Region of São Paulo, where there was a blind child enrolled. It was based on the qualitative character and constituted as a case study. The participants were: a blind child, the two teachers of the nursery class, the coordinator and deputy director of the daycare. For data collection, simple observation of this class routine was performed essentially in relation to the playing, on two occasions: March and April 2012; and June 2012. Instruments were recording field notes, photographs and video recordings. After the observation, interviews were held based on staves, having two teachers, the coordinator and the deputy director as respondents. The results revealed that children with visual impairment use their remaining senses in contexts of playing; the importance of work orientation and mobility from the early years; and, moreover, the need for action of the educator as a mediator in situations of playing to leverage the development of children and especially their language.